Syntax-Information Structure Interactions in the Sentential, Verbal and Nominal Peripheries - Jiménez-Fernández, Ángel (Cambridge Scholars Publishing, 2020)
This book considers the connection between information structure and syntax, exploring formal explanations to account for the distribution of discourse-based phenomena such as topic preposing and focus fronting across languages, with a particular focus on English and Spanish. It discusses issues such as word order and the diverse conditions under which types of topics and foci are licensed in different contexts. It shows the different behaviors of languages with respect to specific discourse-oriented operations to be the consequence of feature inheritance, which takes place in the different pe.